2011
DOI: 10.3109/09638237.2010.542787
|View full text |Cite
|
Sign up to set email alerts
|

Using electronic patient records to assess the impact of swine flu (influenza H1N1) on mental health patients

Abstract: Research databases using electronic clinical records are a useful way to track responses to emerging public health threats. Children receiving mental health care and patients with neurotic and somatoform disorders may be particularly psychologically vulnerable to infectious disease epidemics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 12 publications
5
46
0
4
Order By: Relevance
“…Indeed, contamination fears and washing rituals were exacerbated in OCD patients during the recent H1N1 swine flu pandemic [64]. Planners need to bear in mind the possible social costs of pandemic awareness campaigns and consider the need for additional support services.…”
Section: Disgust and Psychological Welfarementioning
confidence: 99%
“…Indeed, contamination fears and washing rituals were exacerbated in OCD patients during the recent H1N1 swine flu pandemic [64]. Planners need to bear in mind the possible social costs of pandemic awareness campaigns and consider the need for additional support services.…”
Section: Disgust and Psychological Welfarementioning
confidence: 99%
“…With regards to the H1N1 vaccine, Savas found that individuals Turkish healthcare workers with higher levels of state anxiety was found among Turkish healthcare workers who believed the vaccination was unsafe [28]. Additionally, one study demonstrated that individuals with somatoform or anxiety problems, particularly Obsessive Compulsive Disorder, a disorder in which fear of contamination features prominently, exhibited an exacerbation of their psychiatric symptoms as a result of fears related to H1N1 [29]. To the best of our knowledge, no study has examined how individual differences in intolerance of uncertainty or coping style may influence health behaviour, including the decision to be vaccinated, in relationship to the H1N1 virus.…”
Section: Introductionmentioning
confidence: 99%
“…A case-control study based on electronic records concluded that children with obsessive compulsive disorders had a higher likelihood (OR: 8.1; 95% CI: 3.0, 21.3) of expressing moderate/severe concerns about in uenza virus than the norm peers. 25 Children who had a history of somatic symptom disorder (SSD), autism spectrum disorder (ASD), and attention de cit hyperactivity disorder (ADHD) were also reported to experience an exacerbation of psychological symptoms. [26][27][28] Emotional needs…”
Section: Psychological Impactmentioning
confidence: 99%
“…33 However, the mass media may also be considered a source of concern. 24,25 The young were susceptible to social media coverage because they worried that the bad events reported in media would fall on their family, which dramatically triggered anxiety and panic. 25,29 Other impact factors Individual personality, parents' occupation, and residence were also corresponded to children's psychological responses.…”
Section: Medium-term Psychological Effectsmentioning
confidence: 99%
See 1 more Smart Citation